A way out of pay-as-you-go without a double burden - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
It has repeatedly been proposed to reduce conventional pay-as-you-go-systems to a base level, leaving advanced retirement provision for private funded systems. However, pay-asyou-go systems are, in a sense, one way roads, with no available Pareto efficient way out. The paper discusses a combined public debt and taxing strategy which distributes the transition burden equally between future generations, leaving them with only moderate losses in terms of present value. It is shown within both a two generations model and a multiple-generations model of OLG type, that, with this strategy, there results only a temporary increase in public debt ratio, which even turns into a public surplus in the long run. The paper argues that such a transformation towards a base pension system would be both economically advisable and politically feasible.
Keywords: 330